On Maritz' estimates of regression coefficients : extensions, asymptotic distribution and hypothesis testing - Macalalag, Emmanuel B. (Animo Repository, 1988)
A study by Theil proposed an estimator for B with the two-parameter modely = a + B xi + Ei, i = 1, 2, . . . , n, where the errors Ei are symmetrically distributed around zero. Maritz (1979) followed Theil's (1950) argument and came up with an estimator for a in the same model. It is found that the estimators proposed by Theil and Maritz were simple to computer. This paper mainly investigates some of the desirable properties of the Maritz' estimates and extends them to the estimation of B in the multiparameter.